(untitled) (Journal of the College of Basic Education, 2022)
This research aims to answer the following question: What is eclecticism in postmodern arts? How were its applications in art? The research took an aspect of postmodern arts, which is pop art (pop art) by artists (Richard Hamilton and Robert Rauschenberg) as a model. The researchers analyzed a painting by the artist, Richard Hamilton, whose name is (just what makes today’s homes so different, so attractive?), which they did. (1956 AD), and they analyzed a painting by Robert Rauschenberg called (Monogram), the year of its completion (1959), and they reached a number of results, including:1- Eclecticism as a concept appeared in the experiences of contemporary art through its association with the sensual or supposed movement, which in itself represents an axis that a number of artists seek and finds a clear echo in its productions.